2023
DOI: 10.1186/s12879-023-07984-9
|View full text |Cite
|
Sign up to set email alerts
|

Twice evasions of Omicron variants explain the temporal patterns in six Asian and Oceanic countries

Abstract: Background The ongoing coronavirus 2019 (COVID-19) pandemic has emerged and caused multiple pandemic waves in the following six countries: India, Indonesia, Nepal, Malaysia, Bangladesh and Myanmar. Some of the countries have been much less studied in this devastating pandemic. This study aims to assess the impact of the Omicron variant in these six countries and estimate the infection fatality rate (IFR) and the reproduction number $${R}_{0}$$ R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…One of the problems is the difficulty of an accurate prediction of the numbers of reported and unreported cases for the COVID-19 pandemic, and similar pandemics for different age classes [146] . Second, the change of Reproduction number in the presence of rapid evolutionary changes of viral agents in variants and sub-variants should be considered to improve the accurateness of epidemiologic modelling of prediction [87] , [147] , [148] . Finally, a lot of confounding and situational factors should be considered for designing accurate measures of preparedness and prediction for future pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…One of the problems is the difficulty of an accurate prediction of the numbers of reported and unreported cases for the COVID-19 pandemic, and similar pandemics for different age classes [146] . Second, the change of Reproduction number in the presence of rapid evolutionary changes of viral agents in variants and sub-variants should be considered to improve the accurateness of epidemiologic modelling of prediction [87] , [147] , [148] . Finally, a lot of confounding and situational factors should be considered for designing accurate measures of preparedness and prediction for future pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…The potential impact of immune imprinting also motivates further studies to understand the effects and limitations of boosters ( 117 ). Reduced effectiveness of vaccines against Omicron strains might also shift initial targets for vaccination coverage in a population upwards, obstructing the relaxation of non-pharmacological interventions ( 118 ). Ongoing viral transmission from viral shedding from convalescent individuals, in addition to cessation of mask usage, may contribute to future surges of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates for during the COVID-19 pandemic in Wuhan, China, range from 3.11 to 6.47 [ 37 39 ], or 1.4 to 6.47 [ 40 ]. With the virus mutations, some scholars have estimated the transmission characteristics of the Omicron variant in five countries including India, Indonesia, Malaysia, Bangladesh, and Myanmar, and found that the range of reproduction number is between 0 and 9 [ 41 ]. The range of basic reproduction number for each series of viruses is shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Some scholars have estimated IFR, finding that the IFR of the early virus is approximately between 0.5% and 1% [ 45 , 46 ]. The infection fatality rate of the Omicron variant in India, Indonesia, Malaysia, Bangladesh, and Myanmar is estimated to be between 0.016% and 0.136% [ 41 ]. The range of IFR is detailed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%